2013
DOI: 10.1080/01431161.2013.793873
|View full text |Cite
|
Sign up to set email alerts
|

How sensitive is the CWSI to changes in solar radiation?

Abstract: Cloud cover drastically and instantaneously reduces net radiation and available energy. Appearance of clouds will therefore alter the surface energy balance and elicit response of plant canopy temperature (T C ). The attenuated shortwave radiation and altered T C during the presence of clouds may subsequently affect the crop water stress index (CWSI). Therefore, to correctly interpret T C measurements, the effect of clouds must be understood. The objective of this work was to study the effect of abrupt changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…The values of GsI rendered almost the same slopes and constants in the regressions to g s even under different meteorological conditions in both glasshouse and field experiments (Figures 2 and 4). The T a -T s and CWSI showed a good relationship with g s under similar meteorological conditions, but the slope or constant of the regression were largely different when the meteorological conditions were largely different, a finding that agreed with results reported by a previous study (Agam, Cohen, Alchanatis & Ben-Gal, 2013). Its stable relationship with g s makes it possible to compare GsI values among different environments.…”
Section: Discussionsupporting
confidence: 89%
“…The values of GsI rendered almost the same slopes and constants in the regressions to g s even under different meteorological conditions in both glasshouse and field experiments (Figures 2 and 4). The T a -T s and CWSI showed a good relationship with g s under similar meteorological conditions, but the slope or constant of the regression were largely different when the meteorological conditions were largely different, a finding that agreed with results reported by a previous study (Agam, Cohen, Alchanatis & Ben-Gal, 2013). Its stable relationship with g s makes it possible to compare GsI values among different environments.…”
Section: Discussionsupporting
confidence: 89%
“…Ben-Gal et al [38] found higher r 2 for the comparison between CWSIs obtained with equations proposed by Jones [23] with values of stomatal resistance and stem water potential in olives. However, Agam et al [31] indicated that the empirical threshold temperature had a better performance for estimating water stress in olives than the methodology proposed by Jones [23] and Berni et al [37] using climatic data. However, Baluja et al [18] found similar results from CWSIs obtained with climatic data and CWSIs obtained with reference surface temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Ancillary information was obtained from an automatic micro-climatic station located near the experimental plot (described in Section 2.4). In this study, net isothermal radiation (R ni ) was assumed equal to the net radiation [30,31]. Net radiation (W·m −2 ), air temperature ( • C), relative humidity (%), and wind velocity (m·s −1 ) were used to estimate upper and lower temperatures.…”
Section: Thresholding Approachesmentioning
confidence: 99%
“…In fact, other climatic and biotic factors have been proven to induce changes on CWSI values, such as VPD, radiation, wind speed, etc. [67,[73][74][75][76].…”
Section: Models' Verification and Variable Reliability As Bulb Biomasmentioning
confidence: 99%